Analisis Proksimat Daging Ikan Sapu Sapu (Pterygoplichthys pardalis) di Danau Sidenreng Sebagai Bahan Baku Pakan - Sumaidi; Surianti; Muhammad Bibin (JSIPi (JURNAL SAINS DAN INOVASI PERIKANAN) (JOURNAL OF FISHERY SCIENCE AND INNOVATION), 2023)
In intensive fish farming, artificial feed contributes greatly to the production cost structure of around 40-89%. Feed is an important input component because besides being able to determine aquaculture technical coefficients such as growth (SGR), survival (survival rate or SR), feed conversion ratio (FCR), biomass, and time of cultivation to analyze the proximate content in the flesh of the blackfish in Lake Sidenreng. The research was carried out in January-February 2023, and the scavenger fish to be studied were taken from Lake Sidenreng, for proximate analysis they were analyzed at the Integrated Biotechnology Laboratory, Faculty of Animal Husbandry, Hasanuddin University. The type of research used in this research is descriptive quantitative. Sampling used a purposive sampling method, namely, purposive sampling by the required sample requirements. The results of testing the proximate content of sap fish were analyzed descriptively to describe its proximate composition with the feasibility of sap fish as a food ingredient or raw material for making feed. Identification of the proximate test broomstick fish meat in Lake Sidenreng, proximate analysis was performed (moisture content, crude protein, crude fat, crude fiber, BETN, and ash), resulting in proximate analysis results for broom fish meat (P. pardalis), having protein content crude (91.11% l), crude mother (0.74%), crude fiber (0.39%), BETN (1.17%), ash (6.59%), water (16.87%). Broomstick fish contains a complete nutritional composition such as protein, fat, crude fiber, BETN, and water, so it can be recommended as a source of nutritious food and used as a raw material for fish and livestock feed.